2012 Editors' Citations for Excellence in Refereeing. (24th September 2013) - Unknown
Abstract : One of the most important services performed for AGU is the conscientious reviewing of submitted papers. Because of the nature of the reviewing process, this service is also one of the least recognized. Every year editors are asked to select the outstanding reviewers from the previous year. The reviewers listed below have been cited by editors of AGU journals and Eos for excellence in refereeing. These individuals are to be commended for consistently providing constructive and thoughtful reviews .